Preconcentration of Silver with the ion-pair of 1,10-Phenanthroline and Tetraphenylborate on Naphthalene - Usami, Shiro; Kijimoto, Hideki; Chand Mehra, Mool; Satake, M. (Asian Journal of Chemistry, 2010)
A solid ion-pair material produced from 1,10-phenanthroline and tetraphenylborate on naphthalene provides a simple, rapid, economical and fairly selective means for the preconcentration of silver from a large volume of the aqueous samples (about 200-fold concentration can be easily achieved). Silver is quantitatively adsorbed on this material in the pH range 2.0 ~ 11.0 in HCl medium and in the concentration range of 1 ~ 8 N HNO3 medium at a flow rate of 1 ml/min. The solid mass from the column is dissolved out with 5 ml of dimethylformamide (DMF) and measured by an atomic absorption spectrophotometer at 328.1 nm. Beer's law is obeyed over the concentration range 0.5 ~ 10 μg of silver in 5 ml of the DMF solution. Seven replicate analyses of a sample solution containing 2 μg of silver gave a mean absorbance of 0.140 with a relative standard deviation of 1.2%. The sensitivity for 1% absorption is 0.013 μg/ml (0.060 μg/ml for the direct atomic absorption spectrophotometric method from the aqueous solution). Various parameters have been evaluated and the method has been employed for the trace determination of silver in various standard materials.